Dirty - Fisher, Chris; Gooding, Cuba, 1968-; Collins, Clifton, Jr.; David, Keith; Jean, Wyclef; Wheatley, Aimee Garcia; Kittles, Tory.; Hauser, Cole, 1975-; Rockett, Eliot; Beveridge, Ryan.; Sony Pictures Home Entertainment (Firm) (Culver City, Calif. : Sony Pictures Home Entertainment, 2005)
A gang member-turned-cop is forced to choose between his conscience and his loyalty. Recruited into an undercover, anti-gang unit of the LAPD, Amrmado Sancho brings his street smarts onto the force that he has sworn to protect. With his partner Salim Adel, the two patrol LA's streets with force.
Title from container.
Special features: "Gettin' dirty"--An inside look at the Dirty premiere; deleted scenes; "Chump" music video by Oh No; skateboarding/breakdancing featurette; audio commentary with writer/director Chris Fisher and director of photography Eliot Rockett.
Director of photography, Eliot Rockett ; editor, Miklos Wright ; music, Ryan Beveridge ; production designer, Anythony Rivero Stabley.
Cuba Gooding Jr., Clifton Collins Jr., Keith David, Wyclef Jean, Aimee Garcia, Tory Kittles, Taboo, Cole Hauser.
MPAA rating: R; for strong violence, pervasive language, some sexual content and drug use.
DVD, region 1, widescreen (1.85:1) presentation; Dolby Digital 5.1 surround, mastered in high definition
Keywords: Police -- California -- Los Angeles -- Drama; Gangs -- California -- Los Angeles -- Drama; Feature films; Thrillers (Motion pictures); Police films; Video recordings for the hearing impaired; French language materials; Thai language materials; Chinese language materials; Korean language materials; Portuguese language materials; Spanish language materials; Los Angeles (Calif.) -- Drama